PEMIKIRAN PAHAM KOMUNIS PERSPEKTIF PANCASILA - Casedi, Edi; Hidayat, Syamsul (Profetika Jurnal Studi Islam, 2017)
Pancasila is the foundation of the Republic of Indonesia were scattered on God, just and civilized humanity, unity of Indonesia, Democracy and led by the wisdom of wisdom in deliberation representation, social justice for all Indonesian people. Belief in God Almighty be a fundamental principle of the five precepts that exist. This precept demands that citizens of the Republic of Indonesia for the godless. However, in reality happened in the history of Indonesia and recognition Indonesian communist party in the election. This study tried to sit communism in the ideology of Pancasila and whether he has a space in it. This research is to answer the question in the hope that people understand and be aware of the teachings of communism when seated on the basis of the Homeland. Be a kind of literary qualitative research with historical and philosophical approach. Results showed communism research from the aspect of ideology, politics, socio-economics is contrary to the principles of Pancasila which are the foundation of the Republic of Indonesia. Thus, by reason of the above teachings and ideology of communism do not have space in Pancasila. Because something in violation not possible to put together and aligned. Because ideology is contradictory and do not have space in the basic state and the nation of Indonesia, should and rightly where this doctrine is not worth living fertile motherland ever betrayed by the PKI to perform a coup over the legitimate government with efforts to make Indonesia not sovereign to make " subordinate "and accomplice of Russia, the communist state.Pancasila merupakan dasar Negara Kesatuan Republik Indonesia yang bersilakan Ketuhanan Yang Maha Esa, Kemanusiaan yang adil dan beradab, Persatuan Indonesia, Kerakyatan dan dipimpin oleh hikmah kebijaksanaan dalam permusyawaratan perwakilan, Keadilan sosial bagi seluruh rakyat Indonesia. Ketuhanan Yang Maha Esa menjadi asas fundamental dari kelima sila yang ada. Sila ini menuntut agar warga NKRI untuk bertuhan. Namun, dalam realitanya terjadi dalam sejarah Indonesia pengakuan dan pengakomodiran partai komunis dalam pemilu Indonesia. Penelitian ini mencoba mendudukkan paham komunisme dalam ideologi Pancasila dan apakah ia mempunyai ruang di dalamnya. Penelitian ini menjawab persoalan tersebut dengan harapan agar masyarakat memahami dan mewaspadai ajaran komunisme ketika didudukkan dengan dasar NKRI. Literer kualitatif menjadi jenis penelitian dengan pendekatan historis dan filosofis. Hasil penilitian menunjukan  komunisme dari aspek ideologi, politik, sosial-ekonomi sangat bertentangan dengan prinsip Pancasila yang merupakan dasar Negara Kesatuan Republik Indonesia.  Maka dengan alasan di atas, ajaran dan paham komunisme tidak mempunyai ruang dalam Pancasila. Karena sesuatu yang bertentanganan tidak mungkin untuk disatukan dan disejajarkan. Karena paham tersebut bertentangan dan tidak memiliki ruang dalam dasar negara dan bangsa Indonesia, sudah seharusnya dan sepantasnya keberadaan ajaran ini tidak layak hidup subur di bumi pertiwi yang pernah dikhianati oleh PKI dengan melakukan kudeta atas pemerintahan yang sah dengan upaya menjadikan Indonesia tidak berdaulat dengan menjadikannya  “bawahan” dan kaki tangan Rusia, negara komunis.